THE PERCEIVED IMPACTS OF GENERATIVE AI ON INDONESIAN EFL MASTER’S STUDENTS’ MOTIVATION IN ACADEMIC WRITING - Edeltrudis Patrisia Soge; Concilianus Laos Mbato (Program Studi PGSD Universitas Flores, 2025)
Academic writing has undeniably become essential in higher education for Master's students of EFL who must publish their work in reputable journals. Unfortunately, maintaining motivation, developing scientific writing, and other independent learning skills remain challenges for many students. The current study examined the role of Generative Artificial Intelligence (Gen AI) in motivating EFL Master's students to write for academic purposes. A mixed-method design with an explanatory sequential approach was employed, involving 34 Master's students at Sanata Dharma University, Yogyakarta. The quantitative data were collected first through a questionnaire and followed by qualitative data, which were collected through semi-structured interviews. The findings revealed that Gen AI tools have a generally positive role in motivating students (r = 0.774, p < 0.01). It is reported that Gen AI helps students improve their writing skills, develop ideas, select vocabulary, and enhance their productivity. On the other hand, students encountered several challenges using Gen AI, such as inaccurate feedback, issues with subscription payment, and an inauthentic voice in writing. The current research uniquely examines Indonesian EFL Master's students, revealing the substantial motivational impact of Gen AI and previously unreported barriers, thereby surpassing prior studies that have focused mainly on cognitive gains or undergraduate contexts.